150-year history of the Hungarian firefighters (Academic Journal of Internal Affairs, 2020)
We celebrate the 150th anniversary of the Hungarian Fire Brigade in 2020. This paper is the written version of my lecture presented at a conference in the Ministry of Interior on the 3rd February 2020. The paper is not concerned with questions, which were touched detailed by other attendants of the conference. My contribution presents a panoramic view of the history of the firefighters and attempts to point out the milestones in the development of the Hungarian Fire Service.
Keywords: fire defence; students’ fire brigade; volunteer fire brigade; factory fire brigade